COVID-19 pandemic: How does stress level affect body weight status in Malaysian adults - Ying, C.Y.; Farah Wahidah, Awi; Anis Syazwina, Salman; Nur Zahirah, Abd Samad; Yokanantini, Muniandy (2021)
Objective Coronavirus disease (COVID-19) pandemic has been taking the world by storm with more cases and deaths were reported throughout the year. People are now exhausted physically and mentally as they do not live their lives the same way before, therefore, this study aimed to investigate how stress level affects body weight status in Malaysian adults during the COVID-19 pandemic. Methodology A total of 705 Malaysian adults (80.7% female, 84.3% Malay) aged from 18 to 59 years old (mean age=30,±11 years) were involved in this cross-sectional study. The data were fully self-administered and collected through an online questionnaire which was distributed via social media. The questionnaire consists of several questions on anthropometric measurements, socio-demographics and stress level which was measured using the validated Malaysian version of Perceived Stress Scale-10 (PSS-10). The simple logistic regression is used to find the association between stress level and body weight status. The data were analysed by using IBM SPSS Statistics Version 22. Results & Discussion Findings showed that 8.8% of the participants were underweight, 50.9% were having normal BMI, 19.6% were overweight, and 20.7% were obese. The overall prevalence of perceived stress was 72.1% (61.7% were moderate stress, 10.4% were high stress). The results from simple logistic regression data analysis showed no statistically significant association between stress level and body weight status (p=0.17). However, perceived stress was significantly more prevalent in Malays (59.9%) (p=0.004), those who were employed (32.5%) and students (32.3%) (p=0.002), and those with no monthly household income (21.1%) (p=0.003). Conclusion Stress level was not statistically correlated to body weight status in Malaysian adults during the COVID-19 pandemic. However, those who were found to be vulnerable to stress should practice a healthy lifestyle in managing their stress.